Instructor's Mamual to Accompany Reaching your potential : - Throop, Robert K. (Thomson Delmar Learning, 2006)
Reaching Your Potential, Concise Edition, is designed for short courses or for those instructors who prefer a shorter text. Similar to the previous edition, this revised text uses a holistic approach to personal development. Readers are actively involved in improving their intellectual, emotional, physical, and social potential with specific learning experiences. Based on the concept that self-belief is the foundation for success, the text offers interesting pedagogic features to help readers develop a positive understanding of their strengths. The "Whatever It Takes" features profile individuals who have overcome difficulties and achieved success in their lives, providing motivational stories that students can relate to